Student Advisee Management System / Larvenyia Muthusamy - Larvenyia, Muthusamy (2004)
Student Advisee Management System (SAMS) is a web based system developed to help the faculty advisor's to manage advisee's records. This system consists of three modules; admin module, advisor module and student module. Main target users for the system are administrator, advisor and student. It is a secured system whereby only authorized personal can access. SAMS will enable the advisors to add, view, edit, delete and search on student particulars, result appointments meting, and attendance. Meanwhile the students arc alJowed to read only th c in form tions. The administrators will deal with the registration of the system user information and assign them to authorize ID and password. They are also in charge in entering the data on student particulars and result and divide students to advisors. SAMS is important to be developed for it can increases the efficiency of student information management for the advisors to smoothen their way to keep track on their advisee's academic progress. Research on existing systems shows that most of the existing system does not involve student information management modules but function as a general information medium. Waterfall with prototyping has been chosen as the software process model. This project' functional requirement focused on three modules of the system. Adrnin module function is to manage registration, student information and student result. Advisor module focused on managing the student information, student result, meeting/ appointment and attendance. Where by student module focused on adding academic plan browsing on their in formations, result, appointment and meeting. This system ha been tested in three level; unit testing on each functions, integration test within functions of every module and finally system tested as a whole. This system will be very useful to be implemented in faculty advisory system to manage records effectively and efficiently.